Decorative elements and symbolic meanings in Yixing purple clay teapots: a focus on Buddhist-themed decorations - Shi, Lijuan; Harun, Zahirah; Ali Yasin, Siti Maryam; Li, Zhou; Wang, Lizhi (Universiti Teknologi MARA, Perak, 2025)
The decorative elements of Yixing purple clay teapots have long served as carriers of cultural symbolism, with Buddhist themes playing a pivotal role in their artistic expression. This research aims to explore the application characteristics and symbolic meanings of Buddhist themes in the decorative design of Yixing purple clay teapots. The decoration focuses on Buddhist-themed comprised of 1) Buddhist symbolic patterns, 2) imagery of Buddhist artifacts, 3) themes of Buddhist practice, 4) biomorphic designs with form imagery. By examining these elements, this research seeks to reveal how Buddhist-themed decorations enhance the aesthetic value of Yixing teapots while reflecting deeper spiritual and cultural meanings. A qualitative research approach is adopted, utilising a literature analysis method to classify and analyses a wide range of purple clay teapot decoration cases. The findings demonstrate that Buddhist themes are deeply rooted in the decorative design of Yixing purple clay teapots, symbolising purity and enlightenment. These themes enrich the decorative language of purple clay teapots and imbue them with profound cultural significance and aesthetic appeal. This research provides an in-depth case analysis of Yixing teapot decoration design, contributing to the inheritance and development of China’s intangible cultural heritage craftsmanship.